IMPACT OF CRIME ON INTERSTATE TRANSPORT OPERATIONS IN NORTHCENTRAL NIGERIA - Ohida, Muhammed Etudaiye (Journal of Terrorism Studies, 2025)
The study investigated the impact of crime on interstate road transport operations in north-central Nigeria. The study relies on descriptive statistics to describe the features of the populations. 200 questionnaires were purposefully administered to the four major interstate motor parks in the capital of some north-central states (i.e., Minna, Lokoja, Benue, and Lafia) using random sampling techniques. The gathered data was analysed using percentages and charts, while the T-test statistics were used to test the study hypothesis. The result shows that there is a statistically significant influence of crimes on interstate transport operations in north-central Nigeria. The study concluded that improving the safety of the road transport network will motivate transport operators to operate more efficiently on the routes.